Electrostatic Contribution to the Ion Solvation Energy: Over-screening Effect in the Nonlocal Dielectric Response of the Polar Medium - A. Rubashkin, Andrey; A. Vorotyntsev, Mikhail (Current Physical Chemistry, 2016)
Molecular dynamic modeling of the nonlocal dielectric response of liquid water predicts a so-called
Keywords: smeared Born sphere model